2010
DOI: 10.1136/gut.2009.176701
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignant progression in patients with Barrett's oesophagus: a Dutch nationwide cohort study

Abstract: In this largest reported cohort of unselected patients with BO, the annual risk of OAC was 0.4%. Male sex, older age and LGD at diagnosis are independent predictors of malignant progression, and should enable an improved risk assessment in BO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
176
4
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(194 citation statements)
references
References 62 publications
8
176
4
6
Order By: Relevance
“…The incidence of BE is two to three times higher in men than women, and male sex is an independent risk factor for malignant transformation. The conservative estimate of the ten-year cumulative risk of EAC is 3-6% in the absence of dysplasia and 7-13% in the presence of low-grade dysplasia (26,27). On the other hand, high-grade dysplasia can be synonymous with microscopic adenocarcinoma in up to 40% of cases, especially if the Barrett's segment is nodular.…”
Section: Barrett's Esophagus (Be)mentioning
confidence: 99%
“…The incidence of BE is two to three times higher in men than women, and male sex is an independent risk factor for malignant transformation. The conservative estimate of the ten-year cumulative risk of EAC is 3-6% in the absence of dysplasia and 7-13% in the presence of low-grade dysplasia (26,27). On the other hand, high-grade dysplasia can be synonymous with microscopic adenocarcinoma in up to 40% of cases, especially if the Barrett's segment is nodular.…”
Section: Barrett's Esophagus (Be)mentioning
confidence: 99%
“…32 The prevalence of BE was lower in women than in men (Table). 7,19,[40][41][42][43][44][45][46][47][48][49][50][51] A systematic review after analyzing the PubMed database between 1997 and 2011 has shown that the prevalence of BE was lower in women than in men (28 out of 10 337, range 0.03-4.6% vs 70 out of 12 463, range 0.08-8.2%).…”
Section: Prevalence Of Barrett's Esophagusmentioning
confidence: 99%
“…More recently, a large nationwide population-based cohort study in the Netherlands involving BE patients with histologically confirmed SIM revealed that the annual risk of EAC was 0.4 %, and after excluding HGD/EAC cases detected within 1 year after BE diagnosis, the incidence rates were 4.3/1,000 pyrs (95 % CI 3.4-5.5) for EAC and 5.8/1,000 pyrs (95 % CI 4.6-7.0) for HGD/EAC combined [67].…”
Section: Risk Factors For Eac or Dysplasiamentioning
confidence: 99%